Tax Compliance: Between Intrinsic Religiosity and Extrinsic Religiosity - Theresia Woro Damayanti (Journal of Economics, Business, and Accountancy Ventura, 2018)
This study examined the correlation between intention on tax compliance and tax compliance behavior with the moderating variable of religiosity orientation both intrinsic religiosity and extrinsic religiosity. The religiosity orientation in this study used religiosity orientation commitment, which better illustrates the commitment on religiosity orientation in everyday life rather than to the presence of individuals in a place of worship as in previous studies. The population in this study is individual taxpayer in Central Java; the sample is taken using multi-stage sampling technique. By using PLS, this study showed that there was an influence of the intention to comply on tax compliance. External religiosity orientation was proved to strengthen the influence of the intention to comply on tax compliance while intrinsic religiosity orientation was not. Tax authorities can utilize the finding by conducting a collaboration with religious leaders to provide insight for taxpayers that religious considerations should affect business considerations that religious teaching is the most important thing in the daily lives and there should be a balance between religious teaching and physical life.